REMEDIATION OF THERMOCHEMICAL MISCONCEPTIONS USING A PROBLEM-BASED LEARNING MODEL BASED ON MULTIPLE REPRESENTATION - Hidayat, Taupik; Herawati, Netti; Jusniar, Jusniar (UNESA Journal of Chemical Education, 2024)
This research aims to describe students’ misconceptions of thermochemical matter at SMAN 8 Pinrang, and then remediate these misconceptions using a problem-based learning model based on multiple representations. The research method used is descriptive analytics. The subjects of this research were class XI F1 students. The data collection instrument used a misconception test of three-tier multiple-choice thermochemical matter with 20 items and an interview guide. Data analysis was carried out using percentages. The research results show that misconceptions occur in the concepts of system and surroundings, exotherm and endotherm, standard enthalpy formation changes, and determining enthalpy changes based on Hess's law. The misconceptions that occur in these four concepts are 1) students identify the container as a system, 2) in exothermic reactions the temperature of the system will decrease because it releases heat into the surroundings, 3) standard formation reactions are identified as being formed from molecules or other compounds, 4) many The reaction stage can affect the magnitude of the enthalpy change. The average reduction in misconceptions for these four concepts was 44% in the medium category. The average reduction in misconceptions for each student is 43% in the medium category.